Impact of climate change on water resources in Ca River basin - Tuyen, Hoang Minh (VNU Journal of Science: Earth and Environmental Sciences, 2010)
Abstract. Base on Climate Change Scenarios (A2, B2, B1), simulation outputs of river flow show the changes of water resources in Ca River. These results are arguments for water resources planning in Ca River under the climate change situations. Keywords: climate change, water resources, Ca River.